Spermatozoa Obtained From Alpaca vas deferens. Effects of Seminal Plasma Added at Post-thawing - Aisen, Eduardo G.; Huanca López, Wilfredo; Pérez Durand, Manuel G.; Torres Mamani, Edita; Villanueva Mori, Juan C.; Ousset, María J.; Medina, Víctor H.; Pérez Guerra, Uri H.; Huanca Mamani, Teodosio (Frontiers in Veterinary Science, 2021)
The viscous seminal plasma (SP) is currently a major impediment to the handling of ejaculate and the development of some biotechnologies in South American camelids. The vas deferens-collected spermatozoa of alpacas is a useful technique to avoid this problem. On the other hand, SP contains a large protein component that has been implicated in the function of spermatozoa within the female reproductive tract. In this sense, the low fertility achieved using transcervical insemination with frozen-thawed spermatozoa in alpacas could be improved by adding SP. This study aimed to evaluate the effect of the whole SP on some in vitro parameters of alpaca spermatozoa after the freezing-thawing-process and the fertility after artificial insemination. It would contribute to a better understanding of the interaction between thawed sperm cells and SP. Spermatozoa were obtained by surgically diverted vas deferens. The samples were diluted with a Tris-based extender, packaged in straws, and frozen. At thawing, each straw was divided into two post-thawing conditions: with the addition of 10% of PBS (control) or with 10% SP (treatment). The sperm cells were evaluated using dynamic parameters, sperm cell morphology, and morphometry. Fertility was assessed by an artificial insemination trial. All in vitro parameters were analyzed by ANOVA. A heterogeneity test was scheduled for the fertility trial. After the freezing-thawing process, motility and plasma membrane functionality was improved when SP was added. No differences were found for post-thaw viability between the control and treatment samples. The percentage of normal cells was higher with SP at post-thawing, and a decrease of the presence of bent tailed spermatozoa with a droplet in the SP group was observed. The length of the head spermatozoa was 3.4% higher in the samples with PBS compared to those in which SP was added. Females pregnant at day 25 post-insemination were 0/12 (with SP inside the straw) and 1/10 (without SP inside the straw). In conclusion, the presence of 10% SP at post-thawing improves sperm cells' motility, functionality, and morphology, indicating that it would be beneficial to improve the frozen-thawed alpaca's physiology spermatozoa. More fertility trials must be developed to increase this knowledge.